2022
DOI: 10.1021/acs.est.1c06885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Hydrophobic Silicon Dioxide in the Interfacial Properties of Lung Surfactant Films

Abstract: The interaction of hydrophobic silicon dioxide particles (fumed silicon dioxide), as model air pollutants, and Langmuir monolayers of a porcine lung surfactant extract has been studied in order to try to shed light on the physicochemical bases underlying the potential adverse effects associated with pollutant inhalation. The surface pressure–area isotherms of lung surfactant (LS) films including increasing amounts of particles revealed that particle incorporation into LS monolayers modifies the organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Fumed (pyrogenic) silica is another variety of silica used in various applications due to its low density, high surface area, and high viscosity. Fumed silica nanoparticles were found to incorporate into LS monolayers in an LBT and disrupt structure at the interface, inhibiting the function of LS ( Guzman et al, 2022 ).…”
Section: Narrative Review Of Lung Surfactant As a Toxicological Modelmentioning
confidence: 99%
“…Fumed (pyrogenic) silica is another variety of silica used in various applications due to its low density, high surface area, and high viscosity. Fumed silica nanoparticles were found to incorporate into LS monolayers in an LBT and disrupt structure at the interface, inhibiting the function of LS ( Guzman et al, 2022 ).…”
Section: Narrative Review Of Lung Surfactant As a Toxicological Modelmentioning
confidence: 99%
“…[12][13][14][15][16] Similar experiments have also been undertaken using more complete models of pulmonary surfactant for a limited range of nanomaterials and found a deterioration in surface tension behaviour. [17][18][19][20] For example, using the oscillating bubble technique, the effect of bare and coated polymeric NPs on the surface tension behaviour of a phospholipid mixture with and without the addition of different concentrations of SP-B and SP-C, alone and in combination, was investigated. 21 The study found that SP-C supplemented phospholipid mixtures were more susceptible to biophysical inactivation by bare NP than phospholipid mixtures supplemented with SP-B and that effects were reduced for coated particles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these models may be used to understand how specific chemicals (e.g., contaminants, pharmaceuticals, etc.) modify the structure-function relationship of biomimetic systems [5,[8][9][10][11][12][13][14][15]. However, these model systems are an oversimplification of the complex biophysical framework running in vivo and allow only certain aspects to be mimicked.…”
Section: Introductionmentioning
confidence: 99%